Common pitfalls in statistical analysis: Linear regression analysis - Aggarwal, Rakesh (Perspect Clin Res, 2017)
In a previous article in this series, we explained correlation analysis which describes the strength of relationship between two continuous variables. In this article, we deal with linear regression analysis which predicts the value of one continuous variable from another. We also discuss the assumptions and pitfalls associated with this analysis.